The centenary of public education in Rio Grande do Norte in the perspective of Nestor Lima: an analysis of the work A century of primary education (Research, Society and Development, 2018)
The relation between history and writing allows us to reflect about the discourse and practice of making history. In this way, this article aims to perform a historiographical analysis of Nestor dos Santos Lima's book "A Century of Primary Education", published in 1927, by the occasion of the centenary of the law of October 15, 1827, which deliberated about the creation of schools of “First Letters” in Brazil. Nestor Lima's book is analyzed from the deliberations of Certeau (2002) on the operation historiographical and it is understood as a document-monument, the result of a voluntary or involuntary effort to impose on the future a certain image (LE GOFF, 1990). We pay attention to the social place of the author, his practice and historical writing. In writing the history of primary education, the author uses of statistical data on the progression of primary school in the period, data on enrollments and frequencies, including detailed information about the creation of schools and their locations, as well as complete lists with names of teachers and the schools where they worked in the different villages of the old province. He writes from sources compiled and collected at the Historical and Geographic Institute of Rio Grande do Norte and the Archive of the General Secretariat of the State. By the analysis, we emphasize that the author, in constructing his book as a way of publicizing the various provisions of the Law and its direct and indirect consequences throughout the century, he produced a relevant source for writing the History of Education in Rio Grande do Norte.